Zmiany w przedsiębiorstwie obrotu środków do produkcji rolnej i produktów rolnych - Chrobocińska, Katarzyna; Juchniewicz, Małgorzata (Changes in Enterprise of Turnover of Means for Agricultural Production and Agricultural Products, 2005)
The paper presents analysis changes (called reactive, imposed and adaptation) which had taken place before the integration of Poland with EU. Besides these changes in researched enterprise there had also been innovative ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 91-96